KEBIJAKAN PERLINDUNGAN CAGAR BUDAYA DALAM MELINDUNGI BATU GRANIT RAKSASA (STUDI KASUS DI KECAMATAN BUNGURAN TIMUR KABUPATEN NATUNA TAHUN 2011-2012) - Juliasari, Fitri; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
One giant granite natural resources capable of providing income and the potential for preservation as an iconic tourist destination. Of some rocks that have a large size, may have significance for the history of an area. Therefore there needs to be a safeguard. Safeguards related to what should be done by the Natuna regency administration, such as the Department of Tourism, Environment and Culture Department of Education, because the protection is closely related to the development of the sector and the tourism potential of the region. But so far, the new Natuna District Government issued a Decree on Registration of Objects of Cultural and Attractions About Determination District Natuna yet issued regulations related to tourism potential or even capture, management and utilization of the huge granite rock. The lack of such a reference causes the Department of Tourism, Department of Education and Culture and the Environment Agency can not make a policy in order to protect, preserve existing potential granite.This study aims to identify and analyze policies for the protection of cultural heritage in protecting the giant granite rock in the District of East Natuna regency Bunguran and obstacles encountered. This research was conducted in the District Bunguran East Natuna regency of Riau Islands province, which is the key informants in this study was the first Member of Parliament Commission Natuna Regency, Head of Education and Culture Natuna Regency, Head of Tourism, Head of the Environment Agency, Head East Bunguran, Sepempang Village Head (Stone Russia), headman Ranai City (Batu Tok Footprint Nyong), Environmental Observer, Community Leaders Bunguran East, Granite and Stone-breaking. The data analysis technique used is descriptive analysis kualititatif, with a deductive inference.The research proves that there is no concrete protection efforts undertaken by the Department of Tourism, Department of Education and Culture, Department of Mines and Energy, Promotion Agency. In other words, in carrying out the implementation of the Act has not been done well, however there are some protective measures undertaken departments of Education and Culture, including: rescue by registering stone path that has historical value. While the obstacles faced in the protection of giant granite rocks, consisting of: the absence of clearrules, unavailability of expert rock, no allocation / budget special protection granite, and lack of public awareness.Keywords: Granite Stone, Protection, Heritage